ABER Performance of OFDM-IM systems by RIS design in the presence of IQI and α-μ fading - Karahan, Busra; Develi, Ibrahim; Canbilen, Ayse Elif; Alsalameh, Hussam (Engineering science and technology, an international journal, 2024)
Index modulation (IM) techniques are among the competitive candidates for fifth-generation and beyond (5GB) systems, offering new ways of conveying information thanks to their advantages such as structure flexibility and hardware convenience. Meanwhile, research on orthogonal frequency division multiplexing (OFDM) performance improvements for next-generation wireless communication systems is still intensively ongoing. Accordingly, the IM system has been adapted to OFDM, which allows additional bits of information to be transmitted through the subcarrier indices of the OFDM. Nevertheless, hardware impairments (HWIs) limit the performance of the transceiver. In the literature, reconfigurable intelligent surface (RIS) technology controls the propagation environment and enhances the quality of the received signal by modifying the phase of the incoming signal. In this paper, we investigate the effects of in-phase (I) and quadrature-phase (Q) imbalance (IQI) on RIS-based OFDM-IM transceivers motivated by the benefits of the RISs. Firstly, we present an RIS-assisted OFDM-IM model subject to transmitter and receiver IQI effects. Next, the average bit error rate (ABER) performance of the RIS-assisted OFDM-IM is calculated by the provided mathematical expressions taking the effect of IQI into account. The simulation outputs show that the designed RIS-supported scheme achieves a performance improvement compared to the traditional OFDM-IM under the effect of IQI.